Problemi uvajanja učnociljnega kurikula - Kotnik, Rudi (Sodobna pedagogika, 2011)
The aim of the paper is to clarify the basic concepts of objectives-driven curriculum and to critically examine the conceptual issues related to the design and the implementation of curriculum. Relationship between political positions on the curriculum proposed by Ross is used for the analysis of the implementation of objectives-driven curriculum to Slovenian situation. The result of this analysis shows that one of the reasons for the difficulties in the implementation of Bologna process and the corresponding other processes in education is unclear conceptual framework. Moreover, the objective-driven curriculum as an aim is implemented by the content-driven means.
Keywords: competence; učni cilji; učni dosežki; curriculum; experiental learning; kurikulum; aims; kompetentnost; objectives; izkustveno učenje; outcomes